CG Cartoons-based Jigsaw Classroom Strategy: Eliminating Students’ Social Gaps and Developing their Positive English Writing Learning Outcomes - Telaumbanua, Yohannes; Hasbi, Hasbi; Hendro Saptopramono; Sabriandi Erdian (International Journal of Education, Vocational and Social Science, 2023)
Fact discloses that those taking undergraduate classes have always been naturally colored by assorted differences in social stratifications and this is definitely a blessful godsend. These, however, unwittingly drive segregation whose effects clearly disrupted their social interaction, communication, learning atmosphere, and learning outcomes. This research, therefore, aimed at mitigating the issues (gaps). Observation, interviews, and NTA were techniques for collecting and analyzing qualitative data. The major results found that the Cartoons-based Jigsaw Classroom Strategy can reduce social inequalities, performance gaps, and social conflicts among students. Accordingly, the students strongly acknowledged cultural diversity and accept it as a part of life, succeeded in establishing friendly social rapports, and were capable of improving interpersonal skills, developing intercultural competence, critical thinking skills, and pragmatic competence. More outstandingly, this strategy better improved their learning motivation, engagement, and English writing skills. To wrap things up, EFL classrooms are increasingly diverse every year and cultural diversity is the key issue to embrace so that language teachers succeed in being educators, encourage inclusive classrooms culturally, and ease them to develop their social competence and academic bits of intelligence and achievement.